PERAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK PBB PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA AMBON - Margaretha Matly; Maudy Marla Tanihatu; Victor Pattipeilohy (Jurnal Administrasi Terapan, 2026)
This study aims to analyze the effect of service quality on taxpayers’ compliance with the Land and Building Tax (PBB) at the Collection Division of the Regional Tax and Retribution Management Agency (BPPRD) of Ambon City. The research method used was a quantitative approach with a survey design. The sample consisted of 56 taxpayers selected using purposive sampling technique. The research instrument was tested using validity andreliability tests, and data analysis was carried out through simple linear regression. The results showed that service quality had a positive and significant effect on taxpayers’ compliance with PBB. The coefficient of determination (R²) of 0.860 indicates that service quality explains 86% of the variation in taxpayers’ compliance, while the remaining 14% is influenced by other factors beyond this study. The most dominant service quality indicator was the friendliness and patience of the officers, while the highest indicator of taxpayers’ compliance was adherence to payment deadlines. This, improving service quality at BPPRD Ambon City will have a direct impact on increasing taxpayers’ compliance in fulfilling their tax obligations. Keywords: Service quality1), taxpayers’ compliance2)